Chronic Constrictive Pericarditis. (24th September 2013) - Doustkami, Hossein; Hooshyar, Afshin; Maleki, Nasrollah; Tavosi, Zahra; Feizi, Iraj
Abstract : Constrictive pericarditis (CP) is a rare clinical entity that can pose diagnostic problems. The diagnosis of CP requires a high degree of clinical suspicion. The gold standard for diagnosis is cardiac catheterization with analysis of intracavitary pressure curves, which are high and, in end diastole, equal in all chambers. We present a patient with unexplained dyspnea, recurrent right-side pleural effusion, and ascites. Analysis of the ascitic fluid revealed a high protein content and an elevated serum-ascites gradient. Echocardiography, computed tomography, and cardiac catheterization revealed the diagnosis of CP. He underwent complete pericardiectomy and to date has made a good recovery. The diagnosis of CP is often neglected by admitting physicians, who usually attribute the symptoms to another disease process. This case exemplifies the difficulty in diagnosing this condition, as well as the investigation required, and provides a discussion of the benefit and outcomes of prompt treatment.